Processing Of School Garden Products With Vacuum Frying Technology And Marketing Digitalization In Growing Entrepreneurship And Food Security At The Students Of The Al-Mua’aawanah - Nana Nana; Yanti Sofi Makiyah; Ernita Susanti; Agus Sumantri; Suera Sarah Budiaman; Sandi Septiana; Nenden Nuraeni (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Several Islamic boarding schools in Indonesia have begun to transform to make students able to live independently by entrepreneurship. The pesantren curriculum, which used to only focus on studying, is currently coupled with the existence of an entrepreneurial curriculum. One of the Islamic Boarding Schools that has developed entrepreneurship is the Al-Mu'aawanah Islamic Boarding School, Ciamis Regency by implementing entrepreneurship in the subjects of Prakarya and entrepreneurship (PKWU). PKWU is one of the subjects with the hope that students can produce and create more creative, innovative, increase the value of sensibility to the progress of the times while appreciating technology, local wisdom. In addition, students are expected to be able to become entrepreneurs after producing products that have been made. One of the Prakarya and Entrepreneurship learning activities studied at the Al-Mu'aawanah Islamic Boarding School is the cultivation of kale plants. Santri Pondok Pesantren Al-Mu'aawanah had the idea to process kale into chips. The priority problem of Pondok Pesantren Al-Mu'aawanah after successfully cultivating kale plants is excessive harvest but not supported by maximum processing and marketing. Kale processing is still carried out traditionally, namely not utilizing machine technology in production activities, causing production results to be low. Furthermore, the marketing of kale chips is still done manually, namely that it has not utilized digitalization technology so that the production results cannot be distributed optimally. The rapid development of technology can be used to support kale processing activities, namely using Vacuum Frying technology and the use of digitalization technology for marketing processed kale products based online, one of which is through e-commerce. The methods used in the training activities are lecture methods, question-and-answer discussions, then continued with the practice of making an e-commerce system. This activity is expected to help the students of The Al-Mu'aawanah Islamic Boarding School in growing entrepreneurship and food security. Activities are planned to run for 7 months starting from preparation, implementation of counseling and training, and reporting